(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2018)
Thirty kilometers from the beautiful town of Weldia, on the Weldia Woreta road leading to Gondar, is a small village called Weynie. It is considered a rich village with quite extensive irrigated plots thanks to the small river running all the year-round. Weynie is located at the bottom of a triangular mountain chain connecting Lasta from the northwest, Kobbo (Tigray) from the southeast, and Yejju from the south. Wallie Iyesus is a cave church located in the middle of this triangular mountain chain. Although the church is equally close to Lasta and Tigray – located as it is on the border mountain chain, it is the Yejju inhabitants who are responsible for its upkeep and maintenance. More specifically, Weynie is the village that takes care of Wallie Iyesus and five other churches in the vicinity